PELAKSANAAN KEPPRES NO 54 TAHUN 1980 TENTANG PENCETAKAN SAWAH BARU DI KABUPATEN SUMBAWA - MARIA SARABINA WULY; NI LUH ARININGSIH SARI (GANEC SWARA, 2018)
One of the efforts to utilize the land for national food security, the government in this case the Ministry of Agriculture of the Republic of Indonesia through the Directorate of Expansion and Optimization of Land - Directorate General of Agricultural Infrastructure and Facilities (PSP) initiated the New Rice Fielding Program which is one part of the land reform program that is by opening new agricultural lands or rice fields in various regions, with the hope that strengthening food security will be achieved. This research is a normative research, using primary and secondary data and analyzed with qualitative descriptiveThe results show that 1). The implementation of New Rice Printing according to Presidential Decree No. 54 of 1980 in Sumbawa Besar District has been going well which is marked by the realization rate in some areas in Sumbawa Besar reaching 100%. 2) The obstacles faced by the Sumbawa Besar Regency government towards the implementation of the Baru Sawah Printing based on Presidential Decree No. 54 of 1980 are the lack of facilities and infrastructure and irrigation or irrigation as well as landscape problems so that the efforts made to overcome these obstacles are assisted by the Sumbawa Besar regional government. by the NTB Regional Government and TNI officers tried to provide adequate facilities and infrastructures such as irrigation channel providers, excavators deployment if the location was located in the hills and provided accurate information about the area that would be the place for the implementation of the new rice printing program